Regulation of glucagon secretion by glucose: paracrine, intrinsic or both? - Walker, J; Ramracheya, R; Zhang, Q; Johnson, P; Braun, M; Rorsman, P (2011)
Glucagon secretion is regulated by glucose but the mechanisms involved remain hotly debated. Both intrinsic (within the α-cell itself) and paracrine (mediated by factors released β- and/or δ-cells) have been postulated. Glucagon secretion is maximally suppressed by glucose concentrations that do not affect insulin and somatostatin secretion, a finding that highlights the significance of intrinsic regulation of glucagon secretion. Experiments on islets from mice lacking functional ATP-sensitive potassium channels (K(ATP)-channels) indicate that these channels are critical to the α-cell's capacity to sense changes in extracellular glucose. Here, we review recent data on the intrinsic and paracrine regulation of glucagon secretion in human pancreatic islets. We propose that glucose-induced closure of the K(ATP)-channels, via membrane depolarization, culminates in reduced electrical activity and glucagon secretion by voltage-dependent inactivation of the ion channels involved in action potential firing. We further demonstrate that glucagon secretion measured in islets isolated from donors with type-2 diabetes is reduced at low glucose and that glucose stimulates rather than inhibits secretion in these islets. We finally discuss the relative significance of paracrine and intrinsic regulation in the fed and fasted states and propose a unifying model for the regulation of glucagon secretion that incorporates both modes of control.